Komunikasi Lingkungan Masyarakat Destinasi Wisata Komunikasi Lingkungan Masyarakat di Kawasan Wisata Geopark Meratus Tahura Mandiangin - Chandrabuwono, Achmad Bayu; Sari, Noviana; Waluyo, Bambang Dwi; Aldi Istihsan, Muhammad; Ramadhana, Yasintya Rahmi (Universitas Medan Area, 2025)
This study aims to analyze environmental communication practices in the context of managing the Meratus Geopark natural tourist destination, particularly in the Tahura Sultan Adam Mandiangin area, Banjar Regency, South Kalimantan. The approach used is a descriptive, qualitative one, employing Lasswell's communication model framework and Yenrizal's (2017) concept of environmental communication. The research findings indicate that environmental conservation communication practices remain hierarchical and top-down, with government institutions, particularly the Forestry Department, playing a dominant role in communication. Local communities have not been strategically involved in the process of message delivery or in the formulation of management policies for the area. The messages conveyed tend to be technocratic and have not integrated local cultural wisdom, while the media used include banners, the “bottle cage” trash bin innovation, and social media that have not been systematically coordinated. Feedback from tourists indicates a positive effect on conservation messages, but long-term effectiveness still depends on active local community participation and the strengthening of two-way communication. This study recommends the need to strengthen the role of local actors as communicators, integrate cultural values into environmental messages, and optimize digital media as part of a community-based conservation communication strategy.